Osteoporosis and Related Factors in Patient with Type 2 Diabetes and Prediabetes - Derya Ünal; Kevser Onbaşı; Türkan Paşalı Kilit (Galenos Yayinevi, 2022)
Objective:Osteoporosis is a disease leading to increased morbidity and mortality. Untreated patients are prone to fracture. In consequence, early diagnosis of osteopenia and osteoporosis is important. Diabetes mellitus (DM) is among the leading causes and is associated with an increased risk of skeletal fractures. The high prevalence of osteoporosis and associated fractures is an important health problem. Although many studies have been conducted to evaluate the frequency of osteoporosis in DM, there are only limited data for prediabetes.Materials and Methods:Prediabetes patients and type 2 patients with DM applying to our internal medicine and endocrinology and metabolic diseases outpatient clinics were included in this cross-sectional study. Twenty-nine women and 6 men with prediabetes, and 53 women and 8 men with DM were evaluated. Lumbar spine and femur bone mineral densities were investigated using dual-energy X-ray absorptiometry. The study was conducted in accordance with the Declaration of Helsinki.Results:Lumbar spine T-scores were lower in patients with diabetes. Also, FRAX value for major fracture risk was higher. Prediabetes patients bone mineral density measurements revealed osteopenia. In our study, a major risk factor for osteoporosis was advanced age.Conclusion:Prediabetic patients are at risk of osteopenia and osteoporosis. Therefore, the necessity of preventive measures starting from the prediabetic period is underlined.